Administrações dentro da favela: Organizações dos micros e pequenos empreendimentos na favela da Rocinha na cidade do Rio de Janeiro - cardiano, rafael (2025)
This study aims to characterize the ways of organizing micro and small enterprises in Favela da Rocinha, in the city of Rio de Janeiro. As a methodology, a descriptive case study was used, with a qualitative bias and use of interpretative data analysis. As a result, it was possible to identify that businesses in Favela da Rocinha face negative stereotypes and stigmas, prejudices and a lack of support from the State, which directly affects their professional development and performance. The research revealed that the lack of support from the State and society contributes to the day-to-day difficulties of these entrepreneurs, causing them environmental racism, discrimination, and persistent socioeconomic inequalities, which have a substantial impact on these ventures. The lack of awareness and the perpetuation of stereotypes amplify these challenges, hinder the formation of support networks and encourage impunity through the marginalization of entrepreneurs and residents of Favela da Rocinha.